Evaluation of Deformation and Permeability Behavior of Amygdaloidal Basalt under a Triaxial Cyclic Loading Creep Test - Long Yan; Weiya Xu; Biao Li; Hua Ji; Jinjian Gu (Geofluids)
Amygdaloidal basalt is a typical rock mass in the dam foundation of the Baihetan hydropower project in southwest China. With rising and drawdown of the reservoir water level, the permeability and creep deformation characteristics of the amygdaloidal basalt are much complicated in the long-term cyclic loading processes. A cyclic loading-unloading creep test on the amygdaloidal basalt was performed to evaluate its deformation and permeability behavior. The results showed that Poisson’s ratio and elastic modulus of the rock specimen varied significantly under different loading processes with a relatively large irreversible deformation. The permeability and strain rates of rock changed in two phases under lower deviatoric stresses, while there are three typical stages of strain growth with the final stress level of 121.8 MPa. For axial stress of 128 MPa, the creep deformation and creep rate in the axial direction are smaller than these in the lateral direction. Before the sample failure, the lateral deformation accelerates earlier than the axial deformation. The results also suggested that the permeability of the rock specimens decreases considerably during each loading process and then tends to be constant with time. No apparent change in steady permeability is observed with variation of stress. For 128 MPa axial stress, the permeability first decreases, then tends to be in a stable value, and at last increases during the sample failure.